Eucosma callei sp. nov.—a new species of Olethreutinae from South-eastern Iberian Peninsula (Lepidoptera, Tortricidae) - Girdley, John; Garre, Manuel; Rubio, Rosa María; Ortiz, Antonio S. (Zootaxa, 2025)
Eucosma callei sp. nov. is described and illustrated from the Iberian Peninsula. It differs from its Iberian congener, Eucosma gonzalezalvarezi Agenjo, 1970, in external appearance and genitalia. The 5’ barcode fragments of the mitochondrial gene COI (the DNA barcode) are presented and confirms the description of this new species.